Clinical and metabolic profiles of very severely obese pregnant women and their associations with birth weight. (18th April 2012) - Forbes, S; Reynolds, RM; Harold, G; Howie, F; Denison, FC; Norman, JE
Abstract : Introduction: During gestation diminished maternal insulin sensitivity (IS) increases the availability of fuels allowing fetal growth. Class III obesity (OB; BMI≥40kg/m2) is associated with reduced IS but it is not known how nutrient availability differs and how this impacts on birth-weight versus normal pregnancies (CON). Methods: 213 OB (median(interquartile range) 43.2(41.1-46.3)kg/m2) and 87 CON (BMI 22.6(21.2-23.5)kg/m2) pregnant Caucasians had maternal anthropometrics, fasting glucose, NEFA and insulin concentrations recorded at 16, 28 and 36 weeks(wk). Premature births (4 OB, 1 CON) were excluded. Results: Weight gain (WG) was greater in CON vs. OB (10.4(7.6-13.0)kg vs. 5.2(2.4-8.3)kg; p<0.0001; 16-36wk). Glucose, NEFA and insulin were higher in OB vs. CON throughout pregnancy (p<0.0001). IS was lower in OB vs. CON (p<0.0001), decreasing with gestation (all p<0.02). Glucose peaked at 28wk: OB (16wk 4.5(4.2-4.7)mmol/l; 28wk 4.6(4.3-4.9)mmol/l; 36wk 4.5(4.1-4.8)mmol/l; p=0.05) and CON (16wk 4.2(4.1-4.4)mmol/l; 28wk 4.2(4.0-4.5)mmol/l; 36wk 4.1(3.9-4.3)mmol/l; p=0.0003). NEFA troughed at 28wk: OB (16wk 0.49(0.41-0.60)mmol/l; 28wk 0.44(0.37-0.55)mmol/l; 36wk 0.50(0.39-0.61)mmol/l; p=0.005) and CON (16wk 0.31(0.25-0.40)mmol/l; 28wk 0.29(0.22-0.36)mmol/l; 36wk 0.33(0.27-0.46)mmol/l; p=0.03). Birth weights after adjusting for gestational age, gender, parity, smoking and social-class were greater in OB 3610(3280-3980)g vs. CON 3600(3260-3860)g (p=0.03). In multivariate regression, 36wk glucose in OB (p=0.03) versus 28wk NEFA, BMI and WG in CON were associated with birth-weight (all p<0.05). Conclusion: OB women were more insulin resistant vs. CON during pregnancy, with greater glucose, NEFA and insulin concentrations and greater adjusted birth-weights. Glucose was associated with birth weight in the OB and NEFA in the CON which may indicate altered fetal preference for metabolites during these pregnancies.